The Implementation of Discretion in Determining the Submission of Time for Land Registration by the Land Office - Wigati, Rina Sari (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The existence of regulations regarding land registration and procedures for settling land disputes is a must, but it also becomes another problem when the applicable regulations are deemed not to be in favor of the interests of a person, group or legal entity. In carrying out government tasks and serving the public, policy-making authority is focused on government positions carried out by government officials, discretionary power is closely related to the obligations, duties and functions of modern government under the rule of law to strive for general welfare through public service. This study uses a Juridical Sociological legal research approach which in this case is used to find out what problems arise related to Discretion in Determining the Time for Filing of Land Registration by the Madiun Regency Land Agency Office or the method of collecting data consisting of document studies or library materials as well as interviews . In carrying out its public service mandate. The National Land Agency, in this case the Head of the National Land Office, has the authority to issue discretionary policies regarding time limits for applications for land blocking and to continue the process of applications for registration or registration in accordance with applicable laws and regulations. In the end it is understandable that the national land agency does not have any interest in matters of land disputes but it is imperative to find or provide solutions in terms of problems that arise in the area of the Head of the Madiun Regency Land Agency Office so that there is no confusion of information, unclear status of the applicants, and no There is a legal vacuum in it, discretion which is the policy of state officials is aimed at allowing a public official to carry out a policy that is slightly contrary to the law as long as it is based on the public interest. Keywords: Discretion; Land; Office; Registration.